(untitled) (Journal of Economic Research & Business Administration, 2015)
The article discusses innovative breakthrough points, proves the necessity of development of the national economy ahead of the curve. An attempt to reveal the actual conditions where the Kazakh companies will increase their competitiveness on the domestic and foreign market has been made. Local manufacturers need to overcome the diffi culties such as stringent lending conditions, depressed stock market, technological dependence on the CIS countries, the limits of the national market, the lack of of managerial personnel, lack of business activity, etc. Kazakhstani tenge devaluation by 20% limits the opportunities for import of the new technologies, equipment, intellectual assets required to run and implement the State Program of Forced Industrial-Innovative Development. The solution for the current situation is seen in the attraction of direct foreign investments through joint ventures and development of the IPO market. However, there is no alternative to creation of a domestic production of goods with a high added value. Kazakhstani companies in processing industries should become a breakthrough and support of the national economy. The growth of their international competitiveness requires an institutional modernization. Many of their characteristics do not comply with an international standards.